Conceptualizing and Validating a Framework of Climate Smart Village in Flood Affected Ecosystem of West Bengal (Indian Journal of Extension Education, 2022)
Climate change is the major issue affecting the survival of human kind in the present day scenario. Farmers are the most vulnerable communities to these changes. Many climate smart technologies were devised and tried to promote through traditional extension system. But their adoption rate is very poor doe to multiple socio-economic and technological factors. Therefore focus extension approach were thought of and concept of climate smart village was introduced to promote climate smart technologies. But the past efforts on establishing climate smart villages were revolved around only on technological dimension ignoring socio-economic dimension of climate change. Hence, the present study conceptualizes the climate smart village integrating technological as well as social factors. The concept has been experimented during 2016-2021 at field level in the village Singimari, Jalpaiguri district of West Bengal in convergence mode with other related stakeholders line Krishi vigyan Kendra (KVK), state agricultural department, National Bank for Agriculture and Rural Development (NABARD), NGOs and farming communities. The findings revealed that adoption level of climate smart technologies and practices has increased significantly after establishment of climate smart village. Therefore, more number of climate smart villages should be established specially in vulnerable ecosystem for better adaptation to climate change.